(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This study examines the key issues and practical directions for improving the efficiency of service enterprises in the context of market economy transformations. The paper identifies the main factors affecting performance efficiency—such as management quality, technological innovation, and human resources—and provides analytical insights into how these enterprises can enhance their competitiveness. Recommendations are presented for implementing digital tools, customer-oriented management, and performance-based evaluation systems.